Perbandingan Kinerja Keuangan PT. Astra Agro Lestari Tbk. dan PT. FKS Multi Agro Tbk Periode Tahun 2017 - 2019 Menggunakan Analisis Du Pont System - Yulia, Iis Anisa (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the comparison of the financial performance of PT. Astra Agro Lestari, Tbk and PT. FKS Multi Agro, Tbk for the period 2017-2019. The analytical method used to assess the company's financial performance in this study is the Du Pont System. The type of the research was a descriptive research. This research used secondary data from PT. Astra Agro Lestari, Tbk and PT. FKS Multi Agro, Tbk from 2017-2019 obtained from IDX. Overall, the financial performance of the two emitens generally fluctuates, so it can be said that the company's financial performance is not in good condition. The results showed that the average financial performance of PT. FKS Multi Agro, Tbk has a better financial performance based on the Du Pont System method than PT. Astra Agro Lestari, Tbk. Keywords: Du Pont System, Financial Statements, Financial Performance